KARAKTERISTIK PENDERITA HEPATITIS B RAWAT INAP DI RUMAH SAKIT UMUM DAERAH DR. PIRNGADI MEDAN TAHUN 2015-2016 - Muhammad Budi Setio Raharjo; Rahayu Lubis; Rasmaliah . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
ABSTRACT                Hepatitis B is a still a public health problem and a cause of death. WHO 2012, Hepatitis B virus (HBV) infects 2 billion of the world's population, about 360 million of whom are chronic Hepatitis B and 600 thousand die from it. To determine the characteristics of Hepatitis B patients in hospital Dr. Pirngadi Medan 2015-2016 Conducted a research with case series design. Population and sample were 120 patients and recorded in hospital medical records. Univariate data were analyzed descriptively while bivariate data were analyzed using Chi-square test, t-test and Anova with 95% CI. Proportion based on sosiodemographics were groups of age >45 years is 56,7%, male 75,8%, islam 83,3%, high school 49,6%, self employed 40,8%, married 78,3% and living in Medan 62,5%. Level of Bilirubin is not normal 79,2%, level of SGOT is high 43,3%, level of SGPT is high 45,8%, level of albumint is not normal 87,5%, type Acute Hepatitis B 50,8%, , average of treatment duration is 8,73 days, not to beneficiaries 47,5 and returned with outpatient 73,4%. There was significant difference between sex and type Hepatitis B (p=0,001), type Hepatitis B and level of Bilirubin (p=0,034), type Hepatitis B and level albumint (p=0,001), average of treatment duration and type Hepatitis B (p=0,002). It’s hoped the hospital Dr. Pirngadi Medan to give advice for Hepatitis B patients acute and chronic to check up serologic and liver function regularly, and it’s hoped the next researcher will research about one of characterictics or some risk factors are more specific. Key words : Hepatitis B, characteristics of patient